Peningkatan kualitas pembelajaran melalui lesson study learning community pada materi “waktu 24 jam” di Sekolah Dasar - Sri Wahyuni; Roro Eko Susetyarini; Wahyu Prihanta; Firdiani Yuliana (University of Muhammadiyah Malang, 2021)
The main task of the teacher in the learning process is to lead participants to achieve their learning goals. Thus, teachers are required to always improve the quality of their learning, one of which is through the Lesson Study Learning Community (LS-LC). The purpose of this research is to describe the implementation of the Lesson Study Learning Community in SD (Sekolah Dasar-Primary School) Junrejo I, in “the 24-hour clock” material. This qualitative research employed a single case study and explained it naturally. The respondents were one teacher and 28-second graders. There were three stages in the implementation of lesson study, namely: plan, do and see. The data collection technique were using documentation and unstructured interview. The data were analyzed in a quantitative and qualitative description. The findings in the planned activity were the collaboration of teachers and lecturers in innovating and creating chapter and lesson design of “the 24-hour clock” material, considering the characteristic of students. In the open class (do the activity), the students were conducting discussions and observations. During learning, the students were comparing digital and non-digital clocks while lecturers and teachers were observing the learning process. In the seen activity, the observation result from teachers and lecturers were revealed. The implementation of Lesson Study Learning Community in grade II SD Junrejo I, on the material